High‐resolution pH imaging using ratiometric chemical exchange saturation transfer combined with biosensor imaging of redundant deviation in shifts featuring paramagnetic DOTA‐tetraglycinate agents. (27th November 2021) - Mihailovic, Jelena M.; Huang, Yuegao; Walsh, John J.; Khan, Muhammad H.; Mishra, Sandeep K.; Samuels, Sara; Hyder, Fahmeed; Coman, Daniel
Abstract : Chemical exchange saturation transfer (CEST) and biosensor imaging of redundant deviation in shifts (BIRDS) methods differ respectively by detecting exchangeable and nonexchangeable proton signals by magnetic resonance. Because CEST contrast depends on both temperature and pH, simultaneous CEST and BIRDS imaging can be employed to separate these contributions. Here, we test if high‐resolution pH imaging in vivo is possible with ratiometric CEST calibrated for temperature variations measured by BIRDS. Thulium‐ and europium‐based DOTA‐tetraglycinate agents, TmDOTA‐(gly)4 − and EuDOTA‐(gly)4 −, were used for high‐resolution pH mapping in vitro and in vivo, using BIRDS for temperature adjustments needed for a more accurate ratiometric CEST approach. Although neither agent showed pH dependence with BIRDS in vitro in the pH range 6 to 8, each one's temperature sensitivity was enhanced when mixed because of increased redundancy. By contrast, the CEST signal of each agent was affected by the presence of the other agent in vitro. However, pH could be measured more accurately when temperature from BIRDS was detected. These in vitro calibrations with TmDOTA‐(gly)4 − and EuDOTA‐(gly)4 − enabled high‐resolution pH imaging of glioblastoma in rat brains. It was concluded that temperature mapping with BIRDS can calibrate the ratiometric CEST signal from a cocktail of TmDOTA‐(gly)4 − and EuDOTA‐(gly)4 − agents to provide temperature‐independent absolute pH imaging in vivo. Abstract : We developed high‐resolution pH imaging involving a hybrid technique that combines BIRDS with ratiometric CEST using a mixture of two paramagnetic lanthanide agents, TmDOTA‐(gly)4 − and EuDOTA‐(gly)4 − . Accurate pH imaging with CEST requires an additional temperature measurement with BIRDS to account for temperature variations across regions.